Mechanisms of FH Protection Against Neovascular AMD - Borras, Céline; Delaunay, Kimberley; Slaoui, Yousri; Abache, Toufik; Jorieux, Sylvie; Naud, Marie-Christine; Sanharawi, Mohamed El; Gelize, Emmanuelle; Lassiaz, Patricia; An, Na; Kowalczuk, Laura; Ayassami, Cédric; et al. (Frontiers in Immunology, 2020)
A common allele (402H) of the complement factor H (FH) gene is the major risk factor for age-related macular degeneration (AMD), the leading cause of blindness in the elderly population. Development and progression of AMD involves vascular and inflammatory components partly by deregulation of the alternative pathway of the complement system (AP). The loss of central vision results from atrophy and/or from abnormal neovascularization arising from the choroid. The functional link between FH, the main inhibitor of AP and choroidal neovascularization (CNV) in AMD remains unclear. In a murine model of CNV used as a model for neo-vascular AMD (nAMD), intraocular human recombinant FH (recFH) reduced CNV as efficiently as currently used anti-VEGF (Vascular Endothelial Growth Factor) antibody, decreasing deposition of C3 cleavage fragments, membrane attack complex (MAC) and microglia/macrophages recruitment markers in the CNV lesion site. In sharp contrast, recFH carrying the H402 risk variant had no effect on CNV indicating a causal link to disease etiology. Only the recFH NTal region (recFH1-7), containing the CCPs1-4 C3-convertase inhibition domains and the CCP7 binding domain, exerted all differential biological effects. The CTal region (recFH7-20) containing the CCP7 and CCPs19-20 binding domains was anti-angiogenic but did not reduce the microglia/macrophages recruitment. The anti-angiogenic effect of both recFH1-20 and recFH-CCP7-20 resulted from thrombospondin-1 (TSP-1) up-regulation independently of the C3 cleavage fragments generation. This study provides insight on the mechanistic role of FH in nAMD and invites reconsider its therapeutic potential.